Extracorporeal shockwave therapy for treatment of superficial digital flexor tendonitis in racing Thoroughbreds: 8 clinical cases - Hunter, J.; McClure, S. R.; Merritt, D. K.; Reinertson, E. (Veterinary and Comparative Orthopaedics and Traumatology, 2004)
Extracorporeal shock wave therapy (ESWT) was administered to 8 racing Thoroughbreds with superficial digital flexor (SDF) tendon injuries sustained during racing or race training. The tendons were assessed ultrasonographically. The ability of the horse to return to racing was monitored. Five of 8 horses raced successfully, 2 re-injured the tendon during retraining, and 1 horse was retired due to age and lesion severity.
Keywords: Superficial digital flexor tendonitis; extracorporeal shockwave therapy